Helicobacter pylori outer membrane vesicles mediate central tolerance in C57BL/6J mice offspring T cells via maternal-fetal transmission - Wei, Yusen; Zhou, Lu; Zhao, Xiaofei; Qiu, Huiqing; Hu, Dailun; Shi, Zhongli (Frontiers in Immunology, 2025)
Outer membrane vesicles (OMVs) released by Helicobacter pylori (H.pylori) can enter the blood circulation of the host and cause extra-gastric lesions such as atherosclerosis and hyperemesis gravidarum. This study aimed to investigate the effect of OMVs released by H.pylori on the development of thymic T cells in offspring mice and its underlying mechanisms. Through experimental observations, we found that H.pylori OMVs were able to cross the placental barrier, leading to a decrease in the number of CD3+ and CD4+ T cells in the peripheral blood of the offspring mice and a decrease in the response of T cells to H.pylori stimulation. After stimulation with OMVs in T cell positive selection experiments, the expression levels of CHMP5, IKK-β, and NF-κB are up-regulated, and the release of cytokines IL-7, IL-2, IL-4, and IFN-γ is simultaneously increased, whereas in T cell negative selection experiments, the expression of JNK is up-regulated, and the expression of CHMP5 and Bcl-2 is down-regulated in E15-16 fetal thymus organ culture. These results indicate that transmission of H pylori OMVs from mother to fetus might be related to the development of central tolerance in offspring T cells. The underlying mechanism may involve an interaction between the OMVs-stimulated pathway and the TCR pathway, although further research is needed to confirm this hypothesis. The study highlights the importance of preventing H.pylori infection during pregnancy and suggests that the effect of centrally tolerated antigens needs to be considered in vaccine design to maximize prevention.